EFFICACY OF POSTERIOR CAPSULE STRETCHING AND ECCENTRIC LOADING ON FUNCTIONAL KINEMATICS AND SERVE VELOCITY IN ADOLESCENT VOLLEYBALL ATHLETES WITH GIRD: A RANDOMIZED CONTROLLED TRIAL - Samer Jaafar Mohsin; Ali Hussien Mnade (Universitas Negeri Jakarta, 2026)
Background. Glenohumeral Internal Rotation Deficit (GIRD) is a significant limitation to athletic performance. Newer research findings suggest that the incidence of Glenohumeral Internal Rotation Deficit (GIRD) amongst young volleyball players stands at around 37.5% (Mine et al., 2024; Wilcox et al., 2021). Objectives. To this end, the current study investigates a novel rehabilitation protocol comprising posterior capsule stretching in association with eccentric strengthening. Method. Twenty-four adolescent athletes were randomly assigned to an experimental (EG) or a control group (CG; n = 12 per group) in a single-blind experimental design. In the experiment group, there was an 8-week targeted stretching protocol together with eccentric training for the external rotator muscles. Results. Statistical analyses indicated that the experimental group significantly outperformed control on each post-test measure (p< 0.001; 95% CI), with large effect sizes Cohen's d > 0.8). Conclusion. The experimental group experienced significant changes in internal rotation range of motion, functional strength and spike serve speed. Combining eccentric loading with targeted stretching appears effective for restoring shoulder kinematic symmetry and performance parameters in young athletes.